Effective or expedient: Market devices and philanthropic techniques. Issue 2 (6th May 2021) - Eyre, Ben
Abstract : Advocates of philanthropy often frame its worth through efficacy. Critical voices counter such narratives by exposing the social construction of these ideas by hegemonic forces. But they do not interrogate concepts of efficacy through close attention to the process of doing philanthropy. To address this gap, this article engages with philanthropy through the anthropology of techniques. Based on three months of participant observation among high‐net‐worth donors and organizations that work with them in the City of London, I argue that attention to expedience (here referring to maximizing funding rather than effects) invigorates critical reflection on "effective philanthropy." Furthermore, I suggest that my ethnographically informed distinction between expedience and efficacy provides me with a new way to engage with philanthropists: demonstrating the relevance of anthropological theory to their practices and concerns rather than simply criticizing them.